Hello Kitty crochet : super cute amigurumi patterns for Sanrio friends - Lee, Mei Li (Quirk Books, 2014)
Hello Kitty Crochet is all about kawaii: the supercute world of Hello Kitty and her friends meets the Japanese art of amigurumi, or crocheted dolls. With 25 cute and easy-to-make projects, Hello Kitty Crochet is as charming and fun as it is simple to follow.